2012
DOI: 10.1212/wnl.0b013e31826aacd4
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic outcomes in retinopathy-negative cerebral malaria survivors

Abstract: Objectives: Patients surviving retinopathy-positive cerebral malaria (CM) are at high risk for the development of epilepsy, developmental disabilities, and behavioral abnormalities. We aimed to establish whether retinopathy-negative CM is also a risk factor for these outcomes. Between 2005 and 2007, survivors of CM and concurrently hospitalized controls in Blantyre, Malawi, were followed to assess the development of neurologic abnormalities. At discharge and every 3 months thereafter, incident cases of epileps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 11 publications
2
36
2
Order By: Relevance
“…A subgroup analysis of those with CM revealed nonstatistically significantly different mortality rates of 21% in those treated with quinine versus 18% in the artesunate arm. Rates of neurologic morbidity in survivors were not affected by antimalarial choice, although the proportion of survivors with neurologic sequelae in this study was much lower than found in more recently published cohort studies of cerebral malaria survivors [10,11]. Artemisinin derivatives are now the treatment of choice for all forms of malaria and are not inferior to cinchona alkaloids for the treatment of CM.…”
Section: Treatment Antimalarialscontrasting
confidence: 65%
See 3 more Smart Citations
“…A subgroup analysis of those with CM revealed nonstatistically significantly different mortality rates of 21% in those treated with quinine versus 18% in the artesunate arm. Rates of neurologic morbidity in survivors were not affected by antimalarial choice, although the proportion of survivors with neurologic sequelae in this study was much lower than found in more recently published cohort studies of cerebral malaria survivors [10,11]. Artemisinin derivatives are now the treatment of choice for all forms of malaria and are not inferior to cinchona alkaloids for the treatment of CM.…”
Section: Treatment Antimalarialscontrasting
confidence: 65%
“…Despite optimal treatment, mortality is 15-22% [7][8][9]. Survivors do not escape unscathed; cohort studies show that approximately one-third of CM survivors have persistent neurologic sequelae [10,11].…”
Section: Worldwide Burden Of Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Longterm follow-up of these children after hospital discharge was not done. Because CM sequelae may develop weeks to months after hospital discharge, 28 this may have also led to misclassification of outcomes in survivors. This misclassification may have been more common in younger children, whose discharge neurologic and developmental examinations may have been more challenging.…”
Section: Discussionmentioning
confidence: 99%